2019
DOI: 10.1101/656553
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Targeting glutamine metabolism enhances tumor specific immunity by inhibiting the generation of MDSCs and reprogramming tumor associated macrophages

Abstract: the development of metastasis and further enhanced anti-tumor immunity. Indeed, targeting glutamine metabolism rendered checkpoint blockade-resistant tumors susceptible to immunotherapy. Overall, our studies define an intimate interplay between the unique metabolism of tumors and the metabolism of suppressive immune cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…In the next section, we discuss the influence of, metabolism with prime emphasis on fatty acid metabolism and storage in MDSC differentiation and their role in cancer progression. Reports by Min Lee Oh et al demonstrate that targeting glutamine metabolism in MDSCs leads to immunogenic cell death (ICD) of the tumor, decreases the recruitment and accumulation of MDSCs while increasing the number of pro-inflammatory macrophages [ 51 ]. A study conducted by Adeshakin et al confirmed the role of lipid accumulation in immunosuppressive MDSCs.…”
Section: Influence Of Fatty Acid Storage and Metabolism In Mdsc And Macrophage Differentiationmentioning
confidence: 99%
“…In the next section, we discuss the influence of, metabolism with prime emphasis on fatty acid metabolism and storage in MDSC differentiation and their role in cancer progression. Reports by Min Lee Oh et al demonstrate that targeting glutamine metabolism in MDSCs leads to immunogenic cell death (ICD) of the tumor, decreases the recruitment and accumulation of MDSCs while increasing the number of pro-inflammatory macrophages [ 51 ]. A study conducted by Adeshakin et al confirmed the role of lipid accumulation in immunosuppressive MDSCs.…”
Section: Influence Of Fatty Acid Storage and Metabolism In Mdsc And Macrophage Differentiationmentioning
confidence: 99%